Objective concurrent feedback on force parameters improves performance of lumbar mobilisation, but skill retention declines rapidly. - Snodgrass, Suzanne J.; Odelli, Rachel A. (Physiotherapy, 2012)
Abstract: Objective: To determine the optimum practice for students to apply lumbar mobilisations with force parameters consistent with an experienced therapist. Design: Thirty physiotherapy students attended three practice sessions over two weeks where they performed lumbar mobilisations on a fellow student. Students viewed feedback on their applied forces (measured using an instrumented treatment table) in real-time on a computer screen. Performance was tested before and after feedback at each practice session and at follow up sessions one week and three months later. Outcome measures: A greater accuracy in manual force application was defined as a smaller difference between each student-applied force parameter (mean peak force (N), force amplitude (N), and oscillation frequency (Hz)), and that previously applied by an expert. Test data from each session was analysed using Friedman''s and Wilcoxon signed rank tests to determine student learning and retention. Results: Students were more accurate after feedback at Session 1 (median difference between student and expert force parameters 7.7N, IQR 3.2–15.3) than before feedback (median 17.5, IQR 7.3–33.6, P <0.001). Increased practice improved performance, with the greatest accuracy after feedback at Session 3 (median 7.0, IQR 3.5–11.9, P <0.01). Retention however was poor, with performance at follow-up sessions no different to baseline. Conclusions: Students apply more consistent and accurate mean peak force, force amplitude and oscillation frequency after practising with objective, concurrent feedback. Additional practice sessions further improve performance, however retention is poor.